2010
DOI: 10.1590/s1806-37132010000400009
|View full text |Cite
|
Sign up to set email alerts
|

O índice BODE correlaciona-se com a qualidade de vida em pacientes com DPOC?

Abstract: Objective: To determine whether the Body mass index, airway Obstruction, Dyspnea, and Exercise capacity (BODE) index correlates with health-related quality of life in patients with COPD. Methods: We evaluated 42 patients with COPD, quantifying the following: lung function parameters; anthropometric variables; exercise capacity, with the six-minute walk test; dyspnea, with the modified Medical Research Council (MRC) scale; the BODE index; and quality of life, with the modified Saint George's Respiratory Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
0
5
1
2
Order By: Relevance
“…Characteristically, these individuals present with dyspnea and effort limitations due to the fixed airflow obstruction (75)-(77). More advanced stages of the disease result in a worse quality of life for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristically, these individuals present with dyspnea and effort limitations due to the fixed airflow obstruction (75)-(77). More advanced stages of the disease result in a worse quality of life for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Age and dyspnea are determinants of HS in both genders. Araujo and Holanda91 determined whether Body mass index, airway Obstruction, Dyspnea, and Exercise capacity (BODE) index correlates with health-related quality of life in patients with COPD. and found that the BODE index score correlated with the scores of all of the mSGRQ domains in COPD patients with FEV(1) <50%.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between this score and FEV 1 was weak although statistically significant (r=-0.19, p=0.02). Similarly, Araujo and Holanda 11 did not detect a significant difference between the SGRQ psychosocial impact scores of two groups of COPD patients with FEV 1 ≥50% predicted and FEV 1 <50% predicted. The study of Verhage et al 15 found no significant correlation between FEV 1 and a variable designated "satisfaction in social relationships", and they did not find any significant differences between patients with GOLD stages II and III with regard to this factor.…”
Section: Discussionmentioning
confidence: 81%
“…The SGRQ psychosocial impact score indicates the aspects related to social and psychological disorders secondary to the disease 21 . Some studies have investigated outcomes related to the psychosocial impact of COPD 11 , 15 , 39 , 42 - 45 . In the present study, the linear regression models to explain this variable did not identify FEV 1 as a significant contributing factor, which corroborates the results of Huijsmans et al 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation